Pengaruh Inflasi, PDRB dan Upah Minimum Terhadap Penyerapan Tenaga Kerja di Provinsi Bali - Indradewa, I Gusti Agung; Natha, Ketut Suardhika (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Population growth in the country of Indonesia progressively increasing in number, as well as population growth in the province of Bali. Population growth will certainly add to the amount of labor. Increasing the number of workers will be a problem in the world of employment if the amount of labor is not proportional to the number of jobs that can absorb them. This problem becomes important considering the close relation to unemployment. High unemployment will increase the probability of poverty, crime, and social phenomena in society-economy. Bali provincial tourism potential it still has a considerable amount of unemployment. This study has the aim to find out how the influence of the three factors which in theory have an impact on employment. The third factor in the Province of Bali is inflation, Gross Domestic Product (GDP) and the minimum wage. The data used are time series data for twenty years from 1994 until 2013. ” The data analysis technique used is multiple linear regression with EViews application. Once testing is done, the results obtained are simultaneous, three independent variables tested had a significant effect, while partial, Gross Domestic Product (GDP) and the minimum wage has a positive and significant influence while inflation has a negative and significant effect on employment in Bali Province year period 1994-2013 ”.
Keywords: Absorption of labor in the Province of Bali, inflation, GDP, and the Minimum Wage